Identification, characteristics and rice growth promotion of a highly efficient cellulolytic bacterial strain, Cellulomonas iranensis ZJW-6, isolated from paddy soil in central China - Wu, Lei; Che, Songhao; Qin, Xueting; Xu, Yufeng; Tian, Shiqi; Zhu, Yuan; Song, Jian; Guan, Yunpeng; Wang, Dongchao; Wu, Meikang; Yang, Xue; Wu, Zhihai; et al. (Frontiers in Microbiology, 2023)
The microbial degradation of lignocellulose is the best way to treat straw, which has a broad application prospect. It is consistent with the idea of agricultural sustainable development and has an important impact on the utilization of biomass resources. To explore and utilize the microbial resources of lignocellulose degradation, 27 lignocellulose degrading strains were screened from 13 regions in China. ZJW-6 was selected because of its 49.6% lignocellulose weight loss rate. According to the theoretical analysis of the experimental results, the following straw degradation conditions were obtained by ZJW-6: nitrogen source input of 8.45 g/L, a pH of 8.57, and a temperature of 31.63°C, the maximum weight loss rate of rice straw could reach 54.8%. It was concluded that ZJW-6 belonged to Cellulomonas iranensis according to 16S rRNA-encoding gene sequence comparison and identification. ZJW-6 is a Gram-positive bacterium that grows slowly and has a small yellowish green colony. To explain the degradation mechanism of lignocellulose, the experiment of enzymatic properties of the strain was prepared and carried out. It was discovered that ZJW-6 has an excellent ability to degrade cellulose, hemicellulose, and lignin, with cellulose and hemicellulose loss rates reaching almost 50% in 4 days and lignin loss rates reaching nearly 30%. Furthermore, ZJW-6 demonstrated lignocellulose degradation under aerobic and anaerobic conditions, indicating the strain’s broad application potential. ZJW-6 was found to be more effective than ordinary humic acid in improving rice soil (available phosphorus, available nitrogen, organic matter) and promoting rice growth in a rice pot experiment (increasing root-shoot ratio, root activity, chlorophyll content and net photosynthetic rate). ZJW-6 plays an important role in promoting the development and utilization of straw resources. It has important significance for the advancement of green agriculture.